Which expression is equivalent to 19x − 6x + 2 and why? 15x, because 19x − 6x + 2 = 13x + 2 = 15x 11x, because 19x − 6x + 2 = 19x − 8x = 11x 2 + 13x, because (19x − 6x) + 2 = 13x + 2 = 2 + 13x 2 − 13x, because (19x − 6x) + 2 = −13x + 2 = 2 − 13x

Respuesta :

So,

All of the options look so ridiculous that I will not bother discussing why they are not equivalent.

However, one option works.
"2 + 13x, because (19x - 6x) + 2 = 13x + 2 = 2 + 13x"

If you simplify the original expression, you will get 13x + 2.  And the only option that is the closest is 2 + 13x, which is the same as 13x + 2, according to the Commutative Property of Addition.

Answer:

Answer is C. Hope this helps.

Step-by-step explanation: